STRATEGI OPTIMALISASI PASAR RAKYAT DI KOTA SEMARANG - Sucihatiningsih Dian Wisika Prajanti (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
One of the national development programs is to increase the popularity of traditional markets. The existence of the traditional market is affected by several aspects, in which one of them is the availability of modern markets that provides a concept of comfort and cleanness. This has contributed to the decline of traditional sellers’ revenue. Another reason which causes the traditional market is not favoured by people is due to the bad condition of the facility provided by the market, the unorderly management, the behaviour of some elements in the market, the changes of consumers’ behaviour who favour to shop some dry basic needs in the modern market also contributes to the process of traditional market marginalization. Therefore, the objective of this research is to identify the condition of the existing traditional markets in Semarang city and the action of optimization strategies for the traditional market in Semarang city. The analysis method being employed in this research is the quantitative description analysis, qualitative description, and SWOT (Strength, Weakness, Opportunity, and Threat) analysis. The result reveals that traditional markets in Semarang city are divided into 6 UPTD amounting to 54 markets in total. From 2012 until 2014, the market which contributed the highest retribution is UPTD Johar, while in 2016 the highest retribution contributor was from UPTD Karangayu. Market revitalization has been done in 14 traditional markets which include Rejomulyo, Dargo, Waru, Bulu, Sampangan, Surtikanti, Purwogondo, Jerakah, Peterongan, Rasamala, Pedurungan, Genuk, Suryo Kusumo, and Penggfaron. The SWOT analysis shows that the total score of each factor could be elaborated as such, Strength (1.89), Weakness (0.76), Opportunity (1.66), and Threat (1.63). Optimization strategies of traditional market in Semarang include (1) improving the market in a periodical schedule, (2) integrating transportation with Semarang public transports, (3) strengthening the organization of market players/elements and the human resources of the traditional markets’ management, (4) refining the system and expanding the parking areas, (5) adding facilities such as lifts or escalators, (6) fixing the drainage system, rubbish management, and the area sanitation, (7) improving the product zoning / grouping in the market, (8) holding some events for activities or promotion, (9) renewing the mindset through intensive training, (10) planning for a more comprehensive and thorough traditional market’s development, (11) periodically controlling or giving warnings to sellers who are doing business activity outside the traditional markets by Satpol PP, (12) fixing or innovating the service for the consumers, (13) including all stakeholders in the markets’ development, (14) creating rules regarding the construction of modern retails.